Efectividad de un programa educativo “Unidos contra la anemia” en el conocimiento materno sobre prevención de anemia ferropénica en niños menores de tres años - Dominguez Chavez, Mónica Karina (2019)
ABSTRACT The present investigation was carried out at the Llacuabamba Health Center, 2018, with the purpose of determining the effectiveness of the educational program "United against Anemia" in maternal knowledge about the prevention of iron deficiency anemia in children under three years of age. The sample universe consisted of 45 mothers who met the inclusion criteria. For data collection, an instrument was applied: Maternal knowledge questionnaire on the prevention of iron deficiency anemia. The results show that before applying the program, 80.0 percent of mothers obtained average level of knowledge, only 15.6 percent of mothers had good knowledge, and 4.4 percent had a bad knowledge level. After the application, 68.9 percent of mothers obtained a regular level of knowledge, while 31.1 percent of mothers had good knowledge about the prevention of iron-deficiency anemia. The educational program was effective in improving the level of knowledge of the mothers (p = 0.045).